1992
DOI: 10.1113/jphysiol.1992.sp019181
|View full text |Cite
|
Sign up to set email alerts
|

Compared effects of serotonin on cervical and hypoglossal inspiratory activities: an in vitro study in the newborn rat.

Abstract: SUMMARY1. Experiments were performed on the brain stem-spinal cord preparation of newborn rats, in which the phrenic and hypoglossal nerves continue to show rhythmic respiratory activity in vitro, in order to compare the effects of serotonin (5-HT) on both activities and to analyse the mechanisms responsible for the depression by 5-HT of the hypoglossal activity.2. Under control conditions, simultaneous recordings of the inspiratory discharges of hypoglossal and cervical roots showed that the two bursts did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
51
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 53 publications
10
51
0
Order By: Relevance
“…The former hypothesis is supported by earlier findings that 5-HT 2A/2C receptor activation induced bronchoconstriction in the adult rat (4) and depressed hypoglossal activity in vitro in brain stem preparations from neonatal rats (2). In contrast, spinal motoneurons were excited by 5-HT 2A/2C receptor agonists, which suggested that 5-HT 2A/2C receptor activation might rather contribute to increase tidal volume in the intact animal by reinforcing chest muscle activity (2). The present observation that DOI induced a decrease in tidal volume raised the issue whether increase in airway resistance may prevail over chest muscle activation in the intact newborn rat.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The former hypothesis is supported by earlier findings that 5-HT 2A/2C receptor activation induced bronchoconstriction in the adult rat (4) and depressed hypoglossal activity in vitro in brain stem preparations from neonatal rats (2). In contrast, spinal motoneurons were excited by 5-HT 2A/2C receptor agonists, which suggested that 5-HT 2A/2C receptor activation might rather contribute to increase tidal volume in the intact animal by reinforcing chest muscle activity (2). The present observation that DOI induced a decrease in tidal volume raised the issue whether increase in airway resistance may prevail over chest muscle activation in the intact newborn rat.…”
Section: Discussionsupporting
confidence: 77%
“…Both an increase in airway resistance and a depression of "pump" muscle activity could explain this response. The former hypothesis is supported by earlier findings that 5-HT 2A/2C receptor activation induced bronchoconstriction in the adult rat (4) and depressed hypoglossal activity in vitro in brain stem preparations from neonatal rats (2). In contrast, spinal motoneurons were excited by 5-HT 2A/2C receptor agonists, which suggested that 5-HT 2A/2C receptor activation might rather contribute to increase tidal volume in the intact animal by reinforcing chest muscle activity (2).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…All concentrations of drugs and exposure times were determined by consulting the literature. When no previous in vitro use of a drug was reported in literature (i.e., SB 242084, MK-212, and Ro 60 -0175), we selected a minimum dosage in the range of 10 -100 M that consistently blocked or activated behavior based on pilot experiments, a common method used to establish a dose of drugs for selective binding to serotonin receptors in mammalian tissues (Gunther et al 2006;Morin et al 1992;Tryba et al 2006). In cases where agonists and antagonists were previously used only in brain slice preparations (Chen et al 2003;Perrier and Hounsgaard 2003), we selected 10 times the dose for our whole brain preparation so that the drugs penetrated the tissue efficiently.…”
Section: Drugsmentioning
confidence: 99%